2019
DOI: 10.2478/prolas-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Application of Metabolomic Analysis in Exploration of Plant Genetic Resources

Abstract: The article addresses the issues of using metabolomic analysis to study genetic resources of cereal crops in order to (1) determine phylogenetic linkages between species (the degree of domestication); (2) within species to describe genetic diversity according to its responses to biotic and abiotic stressors and biochemical characteristics (chemical compounds) determining food, feed and technological quality indicators; and (3) select the most resistant and highest-quality geno-types for complex breeding use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…showed that the range of variability in the metabolomic profile of improved cultivars was significantly narrower than that of wild species. Metabolites, the content of which may have been reduced in the process of domestication and breeding in comparison to wild oats, are identified [2]. Presumably, it might be connected with the selection during oat domestication and a decline of metabolome diversity while "domestication syndrome" traits were shaped [119].…”
Section: Assessment Of Cereal Crop Genetic Resources According To Thementioning
confidence: 99%
See 3 more Smart Citations
“…showed that the range of variability in the metabolomic profile of improved cultivars was significantly narrower than that of wild species. Metabolites, the content of which may have been reduced in the process of domestication and breeding in comparison to wild oats, are identified [2]. Presumably, it might be connected with the selection during oat domestication and a decline of metabolome diversity while "domestication syndrome" traits were shaped [119].…”
Section: Assessment Of Cereal Crop Genetic Resources According To Thementioning
confidence: 99%
“…Presumably, it might be connected with the selection during oat domestication and a decline of metabolome diversity while "domestication syndrome" traits were shaped [119]. The diversity of metabolomic profiles may be lost in the process of selection when highly specialized singleline intensive-type cultivars are developed because this process is always accompanied by a decrease in genetic polymorphism in a breeding object compared with the metagenome of numerous ecotypes, local varieties, and natural races of dozens of wild species [2,119]. A study of naked and hulled oat forms disclosed differences in their metabolites, which serves as an additional justification of the differentiation between these subspecies of common oat [2].…”
Section: Assessment Of Cereal Crop Genetic Resources According To Thementioning
confidence: 99%
See 2 more Smart Citations
“…The classical way to estimate this functional niche is to focus on morphological and functional traits linked to the species strategy that are easier to measure in the field conditions (such as specific leaf area, foliar toughness, …). Numerous studies have combined this conceptual framework with functional foliar traits measurements to explain species coexistence, niche overlap level and thus the competition intensity [17][18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%